Metabolic status, reproductive, and productive performances of transition dairy cows as affected by dietary rumen-protected choline supplementation. - Lunsin, Ratchataporn; Sokantat, Damrongchai; Silvestre, Taina; Neto, Helio Rezende Lima; Koh, Thong Jin; Sun, Fei; Yeanpet, Chittraporn; Pilajun, Ruangyote (Journal of Advanced Veterinary and Animal Research, 2024)
Research articles about the effects of rumen-protected choline (RPC) supplementation on metabolic response, and reproductive and productive performances in transitional dairy cows were reviewed and presented. Analysis was conducted on 32 research papers that were published. The papers examined treatments without RPC supplementation and RPC supplementation levels varying from 10 to 100 gm/day. The feeding duration of RPC started from 40 to 140 days prepartum and continued until 20 to 140 days postpartum in multiparous dairy cows. Studies indicated that adding herbal choline (Cho) to the diet of transition dairy cows resulted in increased milk production and improved milk quality, leading to enhanced energy balance and reduced oxidative stress. The concentration and yield of IgG in colostrum provide passive immunity to dairy newborns and can be enhanced by dietary Cho supplementation. The inconsistent effects of RPC supplementation on reproduction may be due to several factors such as heat stress, genetics, and management. RPC supplementation improved the transition dairy cows’ milk yield and quality, but dosage response was not observed as in the prior publication. Remarkably, the length of RPC supplementation had a positive correlation with an increase in milk yield. Based on this review, 45–50 gm/day dietary RPC supplementation between 3 weeks pre-calving to 8 weeks post-calving is suggested to increase at least 10% milk yield in dairy cows. J. Adv. Vet. Anim. Res., 11(3): 754-761, September 2024 http://doi.org/10.5455/javar.2024.k827